ChemInform Abstract: Palladium‐Catalyzed Hiyama‐Type Cross‐Coupling Reactions of Arenesulfinates with Organosilanes. Issue 37 (22nd August 2013) - Cheng, Kai; Hu, Sai; Zhao, Baoli; Zhang, Xian‐Man; Qi, Chenze
Abstract The title method allows a new, straightforward, and mild access to a wide range of biaryls.